THE INFLUENCES OF JOB SATISFACTION AND JOB PERFORMANCE TO EMPLOYEE TURNOVER INTENTION AT HOTEL YUTA MANADO - Panda, Farry Bobby (FEB Universitas Sam Ratulangi Manado, 2015)
This research purposing to know the influence of job satisfaction and job performance to employee turnover intention and was to find out whether there is significance influence between job satisfaction and job performance to employee turnover intention in Manado Yuta Hotel. The method of this research is saturated sampling and the data is obtained from questionnaire that distributed to the employee of manado yuta hotel. The analysis method are multiple regression analysis, statistical f test, statistical t test and test of the classical assumption. This research collects data from 21 respondents and the results show that job satisfaction significantly influence to turnover intention with Adjusted R Square 0,355 or 35,5%, while 64,5% from other factors. This research make conclusion that the result showed that job satisfaction have positive influence on turnover intention. However, job performance is showed not significantly on turnover intention. Therefore, the company should attempt to increase job performance to improving employee skills with supervision. Keywords: job satisfaction, job performance, turnover intention